Marasmiellus griseobrunneus sp. nov. (Omphalotaceae) from Kerala State, India - Sharafudheen, Shahina A.; Manimohan, Patinjareveettil (Phytotaxa, 2019)
Marasmiellus griseobrunneus sp. nov. is described from Kerala State, India, on the basis of both morphology and molecular phylogeny. This species is characterized by a grayish brown, sulcate-striate pileus with a fimbriate margin, weakly to strongly intervenose lamellae, pip-shaped to short lanceolate or lacrymoid basidiospores, versiform cheilo- and pleurocystidia, subregular hymenophoral trama, and the presence of appressed or ascending setae on the pileipellis and stipitipellis. A detailed description, comparison with both morphologically and phylogenetically related species, photographs of both the basidiocarps and the microscopic structures, and a Maximum Likelihood phylogram, based on the sequence of the Internal Transcribed Spacer region of the nuclear ribosomal DNA, depicting the placement of the new species are provided.